Epoxidation of styrene by anhydrous hydrogen peroxide over boehmite and alumina catalysts with continuous removal of the reaction water - Choudhary, Vasant R.; Patil, N. S.; Chaudhari, Nitin K.; Bhargava, Suresh Kumar (Journal of Molecular Catalysis A-Chemical, 2005)
Boehmite and alumina (obtained from the boehmite by its calcination at different temperatures 300-900degreesC) are active and stable catalysts for the selective epoxidation of styrene by anhydrous H2O2 to styrene oxide with continuous removal of the reaction water. Influence of the catalyst (boehemite) calcination temperature, H2O2/styrene ratio and catalyst loading on the styrene conversion and selectivity for styrene oxide. phenyl acetaldehyde. benzaldehyde and benzoic acid in the epoxidation has been investigated. In the presence of water. the catalyst shows very poor activity and selectivity in the epoxidation. The catalyst also catalyses H2O2 decomposition and hence has optimum loading for obtaining high-styrene conversion in the epoxidation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Alumina; anhydrous hydrogen peroxide; boehmite; Epoxidation of styrene; Styrene oxide

Supported copper oxide as a highly active/selective catalyst for the epoxidation of styrene by TBHP to styrene oxide - Choudhary, Vasant R.; Jha, Rani; Chaudhari, Nitin K.; Jana, Prabhas (Catalysis Communications, 2007)
Liquid phase epoxidation of styrene by anhydrous and aqueous TBHP to styrene oxide has been studied under reflux, using different supported CuO (viz. Cuo/Si-MCM-41, CuO/Al2O3, CuO/Ga2O3 and CuO/In2O3) as easily separable and reusable heterogeneous catalysts. The CuO/Ga2O3 catalyst showed the best performance in the epoxidation by aqueous TBHP. The CuO supported on In2O3 or Si-MCM-41 also showed very good performance in the epoxidation but only by anhydrous TBHP. However, the CUO/SiO2 catalyst, however, showed very good performance in the epoxidation by both the anhydrous and aqueous TBHP. Influence of the reaction conditions (temperature, time and TBHP/styrene ratio) on the epoxidation by aqueous TBHP over the best catalyst (CuO/Ga2O3) has been investigated. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: CuO/Al2O3; CuO/Ga2O3; CuO/In2O3; Cuo/Si-MCM-41; CuO/SiO2; epoxidation; styrene; Styrene oxide; tertiary butyl hydroperoxide

Selective epoxidation of styrene to styrene oxide by TBHP using simple transition metal oxides (NiO, CoO or MoO3) as highly active environmentally-friendly catalyst - Choudhary, Vasant R.; Jha, Rani; Jana, Prabhas (Catalysis Communications, 2008)
Simple transition metal oxides, such as NiO, CoO or MoO3, etc. show high catalytic activity for the selective epoxidation of styrene to styrene oxide by TBHP. The order of choice for different transition metal oxides for epoxidation is NiO > CoO > MoO3 > Cr2O3 > Fe2O3 > ZnO >= U3O8 >> TiO2 >> MnO2. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CoO; epoxidation; MoO3; NiO; styrene; Styrene oxide; TBHP

Supported nano-gold catalysts for epoxidation of styrene and oxidation of benzyl alcohol to benzaldehyde - Choudhary, Vasant R.; Dumbre, Deepa K. (Topics in Catalysis, 2009)
Nano-gold particles supported on different alkaline earth oxides (viz. MgO, CaO, BaO and SrO), Gr. IIIa metal oxides (viz. Al(2)O(3), Ga(2)O(3), In(2)O(3) and Tl(2)O(3)), transition metal oxides (viz. TiO(2), Cr(2)O(3), MnO(2), Fe(2)O(3), CoO(x), NiO, CuO, ZnO, Y(2)O(3) and ZrO(2)), rare earth metal oxides (viz. La(2)O(3), Ce(2)O(3), Nd(2)O(3), Sm(2)O(3), Eu(2)O(3), Tb(2)O(3), Er(2)O(3) and Yb(2)O(3)) and U(3)O(8) [all prepared by depositing gold on corresponding metal oxide support by deposition precipitation (DP) and/or homogeneous deposition precipitation (HDP) method] were evaluated for their catalytic performance in the liquid phase epoxidation of styrene by tert-butyl hydroperoxide (TBHP) to styrene oxide and also in the solvent-free benzyl alcohol-to-benzaldehyde oxidation (by molecular oxygen or TBHP) reactions. For the epoxidation, the catalytic performance (styrene oxide yield) of the most promising nano-gold catalysts prepared by the HDP method was in the following order: Au/MgO > Au/Tl(2)O(3) > Au/Yb(2)O(3) > Au/Tb(2)O(3) > Au/CaO (or TiO(2)). However, for the oxidation of benzyl alcohol to benzaldehyde by molecular oxygen, the order of choice for the most promising catalysts (based on benzaldehyde yield) was Au/U(3)O(8) > Au/Al(2)O(3) > Au/ZrO(2) > Au/MgO. Whereas, when TBHP was used as an oxidizing agent for the benzyl alcohol oxidation, the order of choice for the most promising catalysts was Au/U(3)O(8) > Au/MgO > Au/TiO(2) > Au/ZrO(2) > Au/Al(2)O(3). The catalytic performance of a particular supported nano-gold catalyst was thus found to depend on the reaction catalysed by them. Moreover, it is strongly influenced by a number of catalyst parameters, such as the metal oxide support, the method of gold depositon on the support, the gold loading and also on the catalyst calcination temperature. Nano-gold particles-support interactions seem to play an important role in controlling the deposition of gold ( amount of gold deposited and size and morphology of gold particles), formation of different surface gold species (Au(0), Au(1+) and Au(3+)) and electronic properties of gold particles and, consequently, control the catalytic performance (both the activity and selectivity) of the supported nano-gold catalysts in the reactions. The nano-gold catalysts prepared by the HDP method showed much better catalytic performance than those prepared by the DP, coprecipitation or impregnation method; in general, the HDP method provided supported gold catalysts with much higher gold loading and/or smaller size gold particles than that achieved by the DP and other methods.
Keywords: Benzaldehyde; Benzyl alcohol; epoxidation; Metal oxide supports; Nano-gold catalysts; Oxidation; styrene; Styrene oxide

Kinetics studies and mechanism evolution of the epoxidation of styrene over nanoporous Au doped TS-1 - Saxena, Samidha; Dwivedi, Reena; Bhadauria, Sheenu; Chumbhale, Vilas R.; Prasad, Rajendra (Polish Journal of Chemical Technology, 2010)
{A kinetic investigation of the slurry phase epoxidation of styrene with hydrogen peroxide has been carried out, for the first time, over nanoporous Au doped TS-1 catalyst, in a batch reactor, in the temperature range of 313-333 K. It was found that product selectivity and the rate of reaction are greatly influenced by concentrations of styrene and hydrogen peroxide. Kinetics studies reveal that the mechanism of the reaction is of the ``Redox'' type. The rate equation
Keywords: Au/TS-1; epoxidation; kinetics; styrene; Styrene oxide

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide